Visual Performance in Patients with Neovascular Age-Related Macular Degeneration Undergoing Treatment with Intravitreal Ranibizumab. (21st February 2013) - Sabour-Pickett, Sarah; Loughman, James; Nolan, John M.; Stack, Jim; Pesudovs, Konrad; Meagher, Katherine A.; Beatty, Stephen
Abstract : Purpose . To assess visual function and its response to serial intravitreal ranibizumab (Lucentis, Genentech) in patients with neovascular age-related macular degeneration (nv-AMD). Methods . Forty-seven eyes of 47 patients with nv-AMD, and corrected distance visual acuity (CDVA) logMAR 0.7 or better, undergoing intravitreal injections of ranibizumab, were enrolled into this prospective study. Visual function was assessed using a range of psychophysical tests, while mean foveal thickness (MFT) was determined by optical coherence tomography (OCT). Results . Group mean (±sd) MFT reduced significantly from baseline (233 (±59)) to exit (205 (±40)) (P = 0.001 ). CDVA exhibited no change between baseline and exit visits (P = 0.48 and P = 0.31, resp.). Measures of visual function that did exhibit statistically significant improvements (P < 0.05 for all) included reading acuity, reading speed, mesopic and photopic contrast sensitivity (CS), mesopic and photopic glare disability (GD), and retinotopic ocular sensitivity (ROS) at all eccentricities. Conclusion . Eyes with nv-AMD undergoing intravitreal ranibizumab injections exhibit improvements in many parameters of visual function. Outcome measures other than CDVA, such as CS, GD, and ROS, should not only be considered in the design of studies investigating nv-AMD, but also in treatment and retreatment strategies for patients with the condition.